Greatness is a process : an examination of Jay Z's rise and future in sports agency - Presley, Regina G.; Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
In April of 2018, Jay Z signed international soccer star Romelu Lukaku, which added the first Manchester United Premier League athlete to a growing roster of sport superstars represented by Jay Z's label. This transition into international sports propelled Jay Z and his agency Roc Nation to the #33 position on the Forbes list of Top Sport Agencies. Jay Z had already become officially certified by the National Basketball Players Association and the Major League Baseball Players Association in 2013 and in the National Football League Players Association in 2017. This type of player representation is not new, but Jay Z and his crossover into the sports landscape may cause significant disruption in the sports agency industry. Jay Z has continued to expand and grow his musical empire and embrace new challenges in the world of business. After securing a 10 year, USD 240 million deal for Robinson Cano with the Seattle Mariners in 2013, Jay Z and his team discovered the benefit of star athletes and began signing high-dollar names like Leonard Fournette, Kevin Durant, Yoenis Cespedes, Ndamukong Suh, and Dez Bryant. In addition, Roc Nation Sports also represents the highest paid Running Back in the National Football League on a big-market team, Todd Gurley, who plays for the LA Rams. The music mogul has long embraced the concept of "sportainment," or combining sports with entertainment, but now faces the challenges of growth in a highly competitive market. Did these athletes make the correct decision in signing with Jay Z? This case explores music mogul Jay Z's agency Roc Nation Sports and the disruption and rivalry in the competitive sports agency marketplace.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Jay-Z, -- 1969-; Roc Nation -- Management; Sports agents